One degree, a thousand memories for Robiatul - Siti Nur Azwin, Zulkapri (2022)
KUANTAN, 20 March 2022 – Hailed from Raub Pahang, Robiatul Adawiyah Sapia’i, 26 proved a farmer’s child could pursue study at the university level and excel in her career.